Battery thermal management systems: From conventional approaches to hybrid configurations - Issah, Ibrahim; Noor, M. M.; Kadirgama, Kumaran; Aslfattahi, Navid; Samylingam, L.; Kok, Chee Kuang; Kiai, Maryam Sadat (Elsevier B.V., 2025)
Effective Battery Thermal Management Systems (BTMS) are essential for ensuring the safety, performance, and durability of lithium-ion batteries in electric vehicles. This review provides a comprehensive synthesis of recent developments in BTMS, with particular emphasis on hybrid configurations that integrate air, liquid, phase change materials (PCM), and heat pipe technologies. The advantages and limitations of individual systems are critically examined, followed by a comparative evaluation of hybrid approaches that aim to overcome the shortcomings of single-mode cooling strategies. Special attention is given to design considerations, scenario-based suitability, and the integration of advanced control techniques. The review also highlights emerging research trends, including artificial intelligence-based real-time thermal control, additive manufacturing for customized cooling structures, and digital twin frameworks for predictive monitoring. Finally, a dedicated research outlook is presented, summarizing unresolved challenges such as thermal runaway under hybrid loads, passive material fatigue, and the trade-off between performance and system complexity. This review consolidates recent advances in conventional BTMS approaches and highlights the growing importance of hybrid configurations, offering a comprehensive perspective on their performance, integration challenges, and future opportunities for scalable and sustainable electric vehicle applications.